Analisis Faktor yang Berhubungan dengan Kejadian Malaria di Pulau Papua (Analisis Data SKI 2023) - Maziyyati, Arsyada; Alma, Lucky Radita; Supriyadi, Supriyadi; Ulfah, Nurnaningsih Herya (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Infectious diseases are still common in Indonesia, one of which is malaria. Data contained in the 2023 Indonesian Health Survey (IHS) showed that the highest prevalence of malaria was found in all provinces on the island of Papua. This study aims to determine the relationship between preventive behavior and access to health care facilities with the incidence of malaria.Methods: This study is a quantitative study with analytic observational research design and cross sectional approach.Result: The results of this study showed an association between insecticide-treated bed nets, mosquito bite prevention materials, mosquito repellent, ventilation gauze with malaria incidence and no association between access to health care facilities in the difficult category with malaria incidence.Conclusion : This study explains that there is a significant relationship between insecticide-treated mosquito nets, mosquito repellents, and ventilation screens and the incidence of malaria as protective factors. There is a significant relationship between mosquito bite prevention factors and the incidence of malaria as risk factors, and there is no relationship between access to health care facilities and the incidence of malaria.